Two Decades of Teaching English to Young Learners: A Bibliometric Study - Khasanah, Ramadhani Uswatun; Sucipto, Sucipto; Cahyo, Septian Dwi (Allure Journal, 2025)
English acts as a universal language and has become a vital skill in many fields due to globalization and the quick development of technology. Learning English as a foreign language early on improves learners' access to global knowledge, communication networks, and mobility, which in turn increases their future academic and career chances. The early introduction of English language teaching, also known as Teaching English to Young Learners (TEYL), is one calculated reaction to this worldwide demand. Children in the early phases of formal education are the focus of TEYL, a specialist area of English language instruction. Instruction at this phase frequently utilizes communicative, contextualized, and play-based methodologies. TEYL has become an increasingly important area of study and practice in education. This study employs a bibliometric analysis of TEYL publications for twenty years, it was from 2004 to 2024, using Scopus as the primary data source and VosViewer for analysis. A total of 252 articles were initially identified, which were then screened to 198 high-quality publications. The study reveals three key findings: (1) A gradual increase in TEYL research publications over the past two decades, with a notable surge in 2022, indicating growing interest in the field. (2) Indonesia has emerged as the leading contributor to TEYL research during this period. (3) Co-occurrence analysis of keywords shows a significant expansion in research topics related to Young Learners. These findings highlight the evolving trends and growing attention to TEYL in the global research landscape.